Pengaruh Penyaluran Kredit, dan Dana Pihak Ketiga (DPK) Terhadap Profitabilitas Lembaga Perkreditan Desa (LPD) di Desa Pakraman Ubud Tahun 2015-2018 - Kadek Gita Dwi Cahaya Putri; I Made Sara (Scopus ID: 57207688235); I Gusti Ayu Athina Wulandari; Kompiang Bagiada (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2020)
LPD is one of the institutional elements of Pakraman Village which is carries out the financial function of Pakraman Village to manage the financial potential of Pakraman Village. This institution is very potential and has been proven in advancing the welfare of the village community and meeting the interests of the village it self. This research aims to determine the effect of lending, and third party funds on the profitability of LPDs in the Pakraman village of Ubud from 2015 to 2018. This research uses 1 Village Credit Institution (LPDs) in 4 years of observation, in order to obtain 48 sample observations with using multiple linear analysis methods. The results of the research indicate that the t test on the variable lending has a positive and significant effect on the profitability of LPDs, the variable of third party funds has a positive and significant effect on the profitability of LPDs. While the F test results obtained variable credit distribution and third party funds have a significant effect on the profitability of LPDs in Desa Pakraman Ubud.